Using Graph Software in Teaching the Subject of Functions: The Case of Azerbaijan - Malahat Abdullayeva (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, the features of Graph 4.4 software used in mathematics lessons are introduced and the development of students' ability to create and interpret function graphs as a result of using this software is examined. The study was designed and conducted as an experimental study. The sample consists of 46th grade 8th grade secondary school students (24 students in the experimental group, 22 students in the control group). In the experimental group, the topic of functions was taught using Graph 4.4 software. At the end of the application, 2 questions were asked to both groups that required graphing and interpretation to answer. The written answers of the students were analyzed by scoring in three categories as correct, partially correct and false. Throughout the comparison, it was determined that the averages of the experimental group were higher. The findings revealed that the use of dynamic algebra software in mathematics lessons improved students' graphic skills. Although this result obtained from a small sample cannot be generalized, this study shows that the use of Graph 4.4 software in mathematics lessons can be one of the basic teaching tools.